Nuclear medicine and biology - Society of Radiopharmaceutical Sciences ([Pergamon], 1993)
" ... publishes original research covering all aspects of radiopharmaceutical chemistry: synthesis, radiopharmacy, in vitro and ex vivo testing, and in vivo evaluation of molecular probes for PET, SPECT, planar imaging, and autoradiography. These multidisciplinary studies demonstrate the mechanism of localization whether the radioactive substance is based on receptor, enzyme, tumor antigen, or other well-defined biochemistry. The study should also address the sensitivity of the probe to changes in biochemistry, although studies of mechanism alone are acceptable. Contributions on the subject of therapeutic radiopharmaceuticals also are appropriate provided that the specificity of labeled compound localization and therapeutic effect have been addressed."
Keywords: Nuclear medicine : Periodicals; Radiobiology : Periodicals; Nuclear medicine; Radiobiology; Radioisotopes; Nuclear Medicine : Periodicals; Radioisotopes : Periodicals; Nuclear Medicine : periodicals; Radiobiology : periodicals; Radioisotopes : periodicals; Nuclear Medicine; Radiobiology; Radioisotopes; Médecine nucléaire : Périodiques; Radiobiologie : Périodiques; Médecine nucléaire; Radiobiologie; Isotopes radioactifs